Addressing Racism in Behavioral Sciences: Recent Insights in the Experimental Analysis of Fairness and Inequity Aversion. - Tanaka, Celina Yoshie; Maia, Laís; Benvenuti, Marcelo (Behavior & Social Issues, 2024)
Issues related to racism and prejudice have been investigated in the field of behavior analysis through stimulus equivalence and relational responding. In addition to this, racism discussed in social and cultural studies considers the problem to have a larger structural basis and is related to decision making involving unequal income distributions. The experimental analysis of fairness and inequity aversion has shown the influence of social and cultural characteristics on the acceptance or rejection of unequal distributions of resources among different individuals and groups. Race is an important aspect that may influence inequity aversion. This work aims to present some studies conducted on the phenomenon of inequity aversion and relate it to the discussion of structural racism, offering a new approach to solving and investigating this social problem. We explore the role of studies about inequity aversion, how fairness may be modulated by cooperative experiences, and their implications to antiracist practices in the context of behavioral sciences.